2012
DOI: 10.1002/jhm.1958
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative “NPO” as an opportunity for diabetes screening

Abstract: BACKGROUND:Novel preventive care opportunities, such as in hospitalized patients, may merit further investigation in an Accountable Care Organization (ACO) model. As 40% of patients with diabetes are undiagnosed, diabetes screening is an urgent public health need. Screening fasting preoperative patients may present an effective means to identify patients who might otherwise remain undiagnosed.OBJECTIVE:To pilot an inpatient preventive care strategy for diabetes screening that would ascertain prevalence of unre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 21 publications
3
9
0
Order By: Relevance
“…In the present study of 416 orthopedic inpatients, our identification of 22% with known diabetes and 4% with previously unrecognized diabetes is similar to the findings of a South Korean study of 173 patients undergoing elective ankle replacement surgery, in whom known and unrecognized diabetes respectively were identified in 22% and 2.9% of patients [27]. In contrast, in another study of 275 hip, knee and spinal surgical patients, it was found that 12% and 3% had known and unrecognized diabetes, respectively [26]. These studies were limited by their smaller sample sizes, and the use of plasma glucose levels or retrospective chart review to classify diabetes status.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In the present study of 416 orthopedic inpatients, our identification of 22% with known diabetes and 4% with previously unrecognized diabetes is similar to the findings of a South Korean study of 173 patients undergoing elective ankle replacement surgery, in whom known and unrecognized diabetes respectively were identified in 22% and 2.9% of patients [27]. In contrast, in another study of 275 hip, knee and spinal surgical patients, it was found that 12% and 3% had known and unrecognized diabetes, respectively [26]. These studies were limited by their smaller sample sizes, and the use of plasma glucose levels or retrospective chart review to classify diabetes status.…”
Section: Discussionsupporting
confidence: 83%
“…Using a combination of electronic medical records and real-time biochemical measures, we have shown the feasibility of this approach for detection of diabetes in inpatients, representing a window of opportunity to engage with people at high risk whose diabetes may otherwise remain undiagnosed. Furthermore, the automatic inclusion of the diabetes status in the patient’s discharge summary addresses a current deficiency in healthcare transition from the orthopedic wards to the community setting [13, 26]. …”
Section: Discussionmentioning
confidence: 99%
“…In an earlier report of emergency department patients from the same institution, the frequency of undiagnosed diabetes was 10.5%, similar to the 9% observation unit frequency in this report . We were unable to find similar observation unit studies, although our results are similar to newly diagnosed dysglycemia reports from emergency department (range 42–66%) and inpatient settings (range 30–48%) .…”
Section: Resultssupporting
confidence: 69%
“…Furthermore, the haemoglobin A 1c (HbA 1c ) test has allowed diabetes screening to become more easily conducted in the hospital, as its values are not influenced by recent illness or exercise, and patients do not need to fast prior to their blood test . A number of studies have determined the prevalence of undiagnosed dysglycemia in various settings, including inpatient populations and emergency department populations . However, little data exist on patients admitted to an observation unit from the emergency department.…”
Section: Introductionmentioning
confidence: 99%
“…In our survey, participation was higher in females than males, and higher in never than ever smokers, indicating that the efficacy of COPD detection can be increased. Higher participation rates of females have also been reported in other studies conducted in primary-care practices [26,27,28,29,30,31,32]. …”
Section: Discussionsupporting
confidence: 55%